Computational modeling of creep-based fatigue as a means of selecting lead-free solder alloys - Steve Brown (Microelectronics Reliability, 2014)
The primary aim of this investigation was to understand the effect of temperature fluctuations on a number of various solder materials namely SAC105, SAC305, SAC405 and Sn–36Pb–2Ag. To achieve this objective, three different classic joint assemblies (a ball joint, a test specimen joint and finger lead joint) were modeled which provided the foundation for the creep and fatigue behaviors simulation. Anand’s viscoplasticity as a constitutive equation was employed to characterize the behavior of solders numerically under the influence of thermal power cycles (80–150 °C) and thermal shock cycles (−40 to 125 °C). To extend the research outcome for industrial use, two additional research activities were carried out. One of them was to obtain lifetime-predictions of solder joints based on Coffin Manson concept. The other one focused on parameterization to obtain the ideal solder thickness under the consideration of plastic strain and economic benefit.